2020
DOI: 10.1167/iovs.61.4.50
|View full text |Cite
|
Sign up to set email alerts
|

Hyperreflective Stress Lines and Macular Holes

Abstract: To determine the prevalence of a central hyperreflective line in eyes with fullthickness macular holes (FTMH) and lamellar macular holes (LMH) and to elucidate the pathoanatomic importance of this optical coherence tomography (OCT) sign. METHODS. This retrospective analysis evaluated patients with FTMH and LMH at the Stein Eye Institute. Clinical data was collected and SD-OCT volume scans were analyzed for the presence of a central vertical hyperreflective line in 3 separate cohorts: patients with SD-OCT prece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In the present study, we analyzed SD-OCT images of fellow eyes of patients with FTMH. In our cohort of patients, the novel previously described 8,9 OCT finding termed "foveal crack sign" could be seen in 19 of 113 cases (17%). 10 (53%) of these 19 eyes developed a FTMH during the observation period.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…In the present study, we analyzed SD-OCT images of fellow eyes of patients with FTMH. In our cohort of patients, the novel previously described 8,9 OCT finding termed "foveal crack sign" could be seen in 19 of 113 cases (17%). 10 (53%) of these 19 eyes developed a FTMH during the observation period.…”
Section: Discussionmentioning
confidence: 61%
“…In a recent work of Ishibashi et al FCS was shown to precede macular hole formation after vitrectomy in 10 eyes of 10 patients 8 . Scharf et al showed in a recent study, that 50% of the eyes with FTMH displayed the foveal crack sign preceding macular hole formation 9 . In our study, 10 (83%) of 12 cases of FTMH development demonstrated FCS prior to FTMH formation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“… 23 , 24 We suggest that abnormal phagocytosis of the outer segments during the disease process produced the cluster of rotated packets of outer segment disks which had abnormal hyperreflectivity in the outer segment region. The HRDs may also be attributed to the increased reflectivity of the outer segments alone due to mechanical stress 25 or degenerative changes. 26 …”
Section: Discussionmentioning
confidence: 99%